The Biology of P-Selectin Glycoprotein Ligand-1: Its Role as a Selectin Counterreceptor in Leukocyte-Endothelial and Leukocyte-Platelet Interaction - Yang, Jing; Furie, Barbara C.; Furie, Bruce (Thrombosis and Haemostasis, 1999)
Cell-cell interactions mediating leukocyte trafficking, thrombogene-sis and inflammation are crucial for the host defense mechanism. The selectin family of integral membrane proteins includes E-selectin, L-selectin and P-selectin. Selectins mediate tethering and rolling of leukocytes to the vessel wall at the site of inflammation. The counter-receptor for P-selectin and possibly the other selectins is P-selectin glycoprotein ligand-1 (PSGL-1). This review focuses on the properties and biology of PSGL-1.